PENGEMBANGAN MEDIA SPINNING WHEEL BERBASIS POWERPOINT MATERI KEBERAGAMAN SOSIAL DAN BUDAYA SISWA KELAS IV SD - Venna Aliyatul Rohma; Shofi Nur Amalia; Khoirul Wafa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The rapid advancement of digital technology in education has encouraged the development of innovative learning media capable of creating more interactive, engaging, and student-centered learning experiences. However, preliminary observations conducted at UPT SD Negeri Jegu 2 revealed that the teaching of Social and Cultural Diversity in fourth-grade classrooms was still dominated by conventional lecture-based instruction with limited use of learning media, resulting in low student participation, motivation, and engagement. This study aimed to develop a Spinning Wheel learning media based on Microsoft PowerPoint and evaluate its feasibility for teaching Social and Cultural Diversity. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants included 21 fourth-grade students, one subject-matter expert, one media expert, and one classroom teacher. Data were collected through observation, interviews, questionnaires, and documentation and were analyzed using descriptive percentage techniques. The findings indicated that the developed media achieved a validity score of 90% from the subject-matter expert, 85.42% from the media expert, and a teacher response score of 90%, all categorized as highly feasible. The implementation test involving students obtained a score of 79.05%, categorized as good, indicating that the media effectively enhanced student engagement during the learning process. Therefore, the Spinning Wheel learning media based on Microsoft PowerPoint is considered valid, practical, and feasible as an alternative instructional medium to support the teaching of Social and Cultural Diversity in elementary schools. ABSTRAK Perkembangan teknologi digital dalam pendidikan mendorong perlunya inovasi media pembelajaran yang mampu menciptakan pengalaman belajar yang lebih interaktif, menarik, dan berpusat pada peserta didik. Namun, hasil observasi di UPT SD Negeri Jegu 2 menunjukkan bahwa pembelajaran materi Keberagaman Sosial dan Budaya pada kelas IV masih didominasi metode ceramah dengan pemanfaatan media yang terbatas sehingga partisipasi, motivasi, dan keterlibatan peserta didik belum berkembang secara optimal. Penelitian ini bertujuan mengembangkan media pembelajaran Spinning Wheel berbasis Microsoft PowerPoint serta menganalisis tingkat kelayakan penggunaannya pada materi Keberagaman Sosial dan Budaya. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE yang meliputi tahap analysis, design, development, implementation, dan evaluation. Subjek penelitian terdiri atas 21 peserta didik kelas IV, satu ahli materi, satu ahli media, dan satu guru kelas IV. Data dikumpulkan melalui observasi, wawancara, angket, dan dokumentasi, kemudian dianalisis menggunakan teknik persentase. Hasil penelitian menunjukkan bahwa media memperoleh skor validitas sebesar 90% dari ahli materi, 85,42% dari ahli media, serta respons guru sebesar 90% dengan kategori sangat layak. Uji implementasi pada peserta didik memperoleh persentase 79,05% dengan kategori baik, yang menunjukkan bahwa media mampu meningkatkan keterlibatan peserta didik selama pembelajaran. Dengan demikian, media pembelajaran Spinning Wheel berbasis Microsoft PowerPoint dinyatakan valid, praktis, dan layak digunakan sebagai alternatif media pembelajaran yang mendukung proses pembelajaran Keberagaman Sosial dan Budaya di sekolah dasar.